Poa secunda J. Presl (Poaceae): a modern summary of infraspecific taxonomy, chromosome numbers, related species and infrageneric placement based on DNA - Soreng, Robert John; Gillespie, Lynn J. (PhytoKeys, 2018)
Poa secunda J. Presl. s.l. is a morphologically highly variable bunchgrass that is a valuable forage species in western North America. There has been much controversy as to whether multiple taxa should be recognised and at what rank in this taxonomically challenging apomictic complex. Here we propose an infraspecific classification for Poa secunda of six varieties within two subspecies, juncifolia and secunda. New combinations are P. secunda vars. ampla, gracillima, juncifolia, nevadensis and scabrella. Conflicting plastid and nrDNA phylogenies show that P. sect. Secundae is of ancient hybrid origin. Based on this and its distinct morphology, the section is raised to the rank of subgenus. A key is presented for P. secunda infraspecies and closely related non-arctic species. Suppl. materials are provided of chromosome counts for Secundae taxa and D.D. Keck specimen annotations of taxa here included in P. secunda.